Volatile metabolites of endophytic Klebsiella aerogenes from Zingiber zerumbet rhizome and its antagonistic effect on soft rot causative Pythium myriotylum - Harsha, K.; Aswati Nair, R. (Journal of Spices and Aromatic Crops, 2020)
Rhizomes of Zingiber zerumbet collected from their natural habitat and reported earlier to have high zerumbone content were selected for isolation of endophytes. Biochemical and molecular characterization using 16S rRNA sequencing of the endophytes identified the isolates as belonging to genus Klebsiella, Pantoea and Enterobacter. Isolate designated ZzKSD8 identified as K. aerogenes yielded maximal antagonistic activities against P. myriotylum determined as 83.5% ± 0.77. Volatile metabolites produced by ZzKSD8 caused absolute impairment of P. myriotylum hyphal growth compared to control (23.9 ± 0.37 cm). Volatile metabolites were extracted from 48 hour grown stationary phase ZzKSD8 cultures using absolute methanol, ethyl acetate and ethanol (60% v/v). GC-MS metabolite profiling detected alkanes and fatty acid methyl esters as the predominant constituents in the solvent extracts. Major constituents included methyl palmitate (31.37%), methyl stearate (18.57%) and cyclopropaneoctanoic acid, 2-hexyl-, methyl ester (17.05%) in methanol extract; alkanes like tetratetracontane (13.18%) and 2-methyloctacosane (12.10%) in ethyl acetate extracts and 4,22-sigmastadiene-3-one as major metabolite (22.51%) and stigmast-5-en-3-ol, (3.beta) (17.40%) in ethanol extract. Identified metabolites reported to modulate defense strategies in plants against phytopathogens makes ZzKSD8 a potential candidate for development of biological alternatives to control soil-borne soft-rot disease.